‘Hot, Young, Buff’: An Indigenous Australian Gay Male View of Sex Work - Sullivan, Corrinne (Social Inclusion, 2021)
Research has historically constructed youths who are involved in sex work as victims of trafficking, exploitation, poverty, and substance abuse. These perceptions often cast the sex worker as deviant and in need of ‘care’ and ‘protection.’ Rarely seen are accounts that provide different perspectives and positioning of youth engaged in sex work. This article explores the lived experiences of Jack, a young gay cis-male who identifies as Indigenous Australian. Despite being a highly successful sex worker, his involvement in such a stigmatised occupation means that he must navigate the social and cultural perceptions of ‘deviant’ and ‘dirty’ work. This qualitative study explores the ways in which Jack negotiates his work, his communities, and the capitalisation of his sexuality. Drawing on Indigenous Standpoint Theory and wellbeing theory, Jack’s choice of sex work is explored through the intersections of sexuality and culture, with the consequences of Jack’s social and emotional wellbeing emerging as his narrative unfolds.